Ảnh hưởng của niềm tin, thái độ, quy chuẩn đến ý định mua thịt lợn của người tiêu dùng tại TP. Hồ Chí Minh - Nguyen Kim , Nam; Ngo Quang , Huan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This study examines the effects of trust on consumers’ intention to purchase pork based on Theory of Reasoned Action (TRA). We use structural equation model (SEM) to analyze data in standard purchasing situation and a hypothetical food scare. The survey of 249 customers from Ho Chi Minh city reveals that general trust has a positive effect on trust in information sources, attitudes, and subjective norms. Only attitudes affect positively intention in standard purchasing situation, whereas attitudes, subjective norms, and trust in supply chain sources have a positive impact on intention in case of a food scare. The results suggest to the manager the role of general trust and trust in the source of information from the supply chain in an explanation of consumers’ purchase intention. In addition, the findings provide which information sources that consumers are most likely to believe in case of a food scare to management agencies.